POTENSI OBJEK WISATA PEMANDIAN ALAMI SEBAGAI PENDUKUNG PARIWISATA DIKECAMATAN 2X11 KAYU TANAM - Vivitri Alfira; Sri Mariya (DEPARTEMEN GEOGRAFI FIS UNP, 2023)
The objectives of this study were to find the potential of natural bathing tourism objects in 2X11 Kayu tanam district and to analyze the development of natural bathing tourism objects in 2X11 Kayu tanam district. in this study Data collection techniques were used in two ways: 1) questionnaires/questions which were conducted by asking respondents about tourist objects; 2) interviews were conducted by directly asking staff about the potential of natural bathing sites in Area 2X11 Kayu tanam. The results of the study on the potential of tourist objects in Dempo Anailand as seen in the results of the class classification were 34 points. Dempo Anailand was included in the high potential, while the White House Tourist Objects, seen from the class category, scored 26, meaning it was included. In medium potential and the Lubuak Tourism Object Bonta scored 22, meaning it is included in low potential.